PAYMENT OF NEW EXPENSIVE TECHNOLOGIES IN HEALTH CARE ON THE BASIS OF RISKS -SHARING AGREEMENTS: POSSIBILITIES OF APPLICATION IN THE RUSSIAN FEDERATION - L. S. Melnikova (Фармакоэкономика, 2015)
The article sets out the results of analysis of existing models of risk sharing agreements, which are used in foreign countries at reimbursement of costs for public drug supply. The author estimates the opportunities to use risk sharing agreements in theRussian Federation, taking into consideration the existing legislative environment. The role of medical technologies evaluation system is regarded as one of the elements of decision system, which element is necessary for introduction of risk sharing agreements. The article also proposes the specific amendments to applicable law, which are to be made for successful introduction of risk sharing agreement in theRussian Federation